DEV-19. THE ROLE OF COMBAT (COMBINED ORAL METRONOMIC BIODIFFERENTIATING ANTIANGIOGENIC TREATMENT) IN HIGH-RISK AND RELAPSED MEDULLOBLASTOMA: A SINGLE INSTITUTION EXPERIENCE. Issue 2 (22nd June 2018) - Chinnaswamy, Girish; Sankaran, Hari; Bhat, Vasudev; KC, Anand; Saroha, Megha; Prasad, Maya; Vora, Tushar; Sahay, Ayushi; Krishnatry, Rahul; Pungavkar, Sona; Janu, Amit; Gupta, Tejpal; et al.
Abstract: OBJECTIVE: We retrospectively reviewed the efficacy and feasibility of COMBAT metronomic chemotherapy in high risk and relapsed medulloblastoma from April 2011 to December 2016. METHODS: Post-surgery high risk medulloblastoma or relapsed medulloblastoma who were started on COMBAT regimen after completion of conventional therapy were included in this analysis. COMBAT regimen consists of low dose temozolomide, etoposide, sodium valproate and 13-cisretinoic acid administered in 12-weekly cycles. RESULTS: 39 children (median age, 9 years; median follow-up, 27.7 months; male:female ratio, 5.5:1) were started on COMBAT during the study period, of which 19 (48.7%) were started after completion of conventional therapy and 20 (51.3%) were started at relapse. Molecular data was available for 17 children (WNT – n=2; SHH, n=3; Group 3, n=5; Group 4, n =7). 2-year progression free survival (PFS) after starting COMBAT was 83.9% (95%CI: 49.4–95.7) and 25.8% (95% CI: 6.5–51.1%) for upfront therapy and relapsed medulloblastoma at presentation respectively. 2-year overall survival was 92.3% (95% CI: 56.6–98.9%) and 67.4% (95% CI: 41.0–84.0%) for upfront therapy and relapsed medulloblastoma at presentation respectively. Only 1 child developed secondary AML and warranted discontinuation of COMBAT therapy. CONCLUSION: COMBAT regimen is a well-tolerated and effective treatment option after completion of conventional treatment for children with high risk medulloblastoma. Future ongoing studies will further delineate the role of COMBAT in high risk medulloblastoma based on molecular subtypes.